Cross-cultural filmmaking : a handbook for making documentary and ethnographic films and videos - Barbash, Ilisa, 1959-; Castaing-Taylor, Lucien (Berkeley : University of California Press, 1997)
"This handbook is for anyone who wants to make or study documentary and ethnographic films and videos. It provides a step-by-step guide to film- and videomaking - from research and funding, through the "nuts and bolts" of production, to distribution - as well as a thorough orientation to the ethical and aesthetic issues that confront documentarians in the field. Filled with practical illustrations, state-of-the-art technical information, and advice from numerous leading filmmakers and anthropologists, this book is the essential guide for veteran and beginner alike."--Jacket.
pt. 1. Getting Going -- 1. Documentary Styles -- 2. From Fieldwork to Filming -- pt. 2. Nuts and Bolts -- 3. Picture -- 4. Sound -- 5. Film or Video? Medium, Format, and Equipment -- pt. 3. Stages of Filmmaking -- 6. Preproduction -- 7. Production -- 8. Postproduction -- 9. Distribution -- Appendix 1. Release Forms -- Appendix 2. International Television Standards and Electricity Currents -- Appendix 3. Names and Addresses -- Appendix 4. Makes and Models -- Filmography.
Filmography: pages 520-526.
Includes bibliographical references (pages 527-537) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Motion pictures in ethnology; Motion pictures -- Production and direction; Cinéma en ethnologie; Cinéma -- Production et réalisation.; 24.33 direction, production and technique of film; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; PERFORMING ARTS / Film / General; Motion pictures in ethnology; Motion pictures -- Production and direction; Ethnologie; Film; Dokumentarfilm; Filmtechnik; Kulturanthropologie; Video; Documentaires; Etnografische films; Anthropology; Social Sciences; Social & Cultural Anthropology; Films ethnographiques; Ratgeber; Textbooks (form)